Analisis Komparatif Harga Saham Pra Dan Pasca Pemilihan Umum Presiden 2024 (Studi Empiris Pada Perusahaan Indeks LQ45 Yang Terdaftar Di Bursa Efek Indonesia) - Muzakir, Muzakir; Fadillah, Muhammad (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2025)
This study aims to determine whether there is a difference in the average stock prices before and after the 2024 Presidential Election in companies listed under the LQ45 Index on the Indonesia Stock Exchange. The study employs an event study approach. The population comprises 45 companies included in the LQ45 Index, with the entire population used as the research sample through a saturated sampling technique. The data analysis method applied is the Wilcoxon Signed Ranks Test. The results provide empirical evidence that there is a significant difference in the average stock prices before and after the 2024 Presidential Election voting. However, there is no significant difference in the average stock prices before and after the official announcement of the election results for companies listed under the LQ45 Index on the Indonesia Stock Exchange. Keywords: Stock prices, 2024 Presidential Election, LQ45 Index companies.